Infectious exposure, antibiotic use, and multiple sclerosis: A population‐based incident case‐control study. (9th May 2018) - Abdollahpour, I.; Nedjat, S.; Mansournia, M. A.; Eckert, S.; Weinstock‐Guttman, B.
Abstract : Background: The existing reports regarding the potential role of infections as well as antibiotic use in multiple sclerosis (MS) etiology are inconclusive. Objectives: We aimed to investigate the association of viral infections as well as antibiotic use and the risk of developing MS. Materials & methods: This was a population‐based incident case‐control study of 547 incident cases and 1057 general population controls obtained from 22 municipality areas of Tehran (7/8/2013‐17/2/2015). Multiple logistic regression models were used to determine the adjusted associations. Results: Overall antibiotic use for ≥14 days during 3 years before the index date, significantly decreased the odds of MS OR 0.69 (95%CI: 0.53‐0.91, P = .008). The results were consistent for different types of antibiotics, including penicillin OR 0.50 (95%CI: 0.34‐0.75, P = .001) and cephalosporins OR 0.25 (95%CI: 0.12‐0.50, P < .001). History of IM was associated with a more than 5fold increased risk of MS OR = 5.7 (95%CI, 1.28‐25.37). There was no statistically significant association between any other single or cumulative number of viral infections with subsequent risk of MS ( P > .05). Conclusions: Considering the possibility of reverse causation, the results of this large case‐control study suggest that use of antibiotics may be associated with a decreased risk of MS. However, viral disease other than infectious mononucleosis was not associated with MS risk.